Hapusnya Hak Waris Atas Tindak Pidana Pemalsuan Surat Wasiat - Sulastri Yasim; M. Fadhlan Fadhil Bahri; Muh. Chaerul Anwar (Alauddin Law Development Journal (ALDEV), 2022)
This study aims at finding out how the inheritance system in the Civil Code (KUHPerdata) is. Second, to find out how the inheritance rights for the crime of forgery will be unforced. This type of research is library research and the research approach used is a juridical normative approach. The data sources for this research are primary, secondary and tertiary data sources through legislation, books, journals and decisions. The data analysis used are through identifying and classifying the existing data and arranging them systematically. The results of this study indicate that in the inheritance system according to the Civil Code there are two ways of obtaining inheritance, namely: first, obtaining an inheritance based on statutory provisions and second, obtaining an inheritance based on a will. There are restrictions on certain parties which result in the abolition of the right to inherit, which is one of the reasons for committing the crime of forging a will.